2013 IEEE International Conference on Control Applications (CCA) 2013
DOI: 10.1109/cca.2013.6662837
|View full text |Cite
|
Sign up to set email alerts
|

Economically optimal control of batch diafiltration processes

Abstract: An economically optimal operation of batch diafiltration processes is studied. The processes are characterized by complex membrane transport models that adequately describe non-ideal membrane characteristics of real-life systems. We consider the optimization criterion which comprises two conflicting objectives, a minimization of processing time and a minimization of solvent consumption. The problem is treated in the multi-objective form in order to investigate the impact of operational cost factors on optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Consequently, a switching to saturated control (clipping) might occur in the presented scheme in situations where the control inputs (33) or (20) would yield the violation of these bounds.…”
Section: Definition Of Optimal Operationmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, a switching to saturated control (clipping) might occur in the presented scheme in situations where the control inputs (33) or (20) would yield the violation of these bounds.…”
Section: Definition Of Optimal Operationmentioning
confidence: 96%
“…In turn, this solution approach gives us an advantage to further analyze the effect of different operational aspects present in the objective function in the light of the analytical solution at hand. This paper builds upon our preliminary results [32,33] and extends the derivation of the optimal operation of DF processes to cover a wider set of problems found in the literature and practice. It is organized as follows.…”
Section: Introductionmentioning
confidence: 96%
“…This problem can be formulated as a problem of multi-objective optimal control [6]. In [7], it was shown that multi-objective formulation of optimization of the DF process can be solved analytically via Pontryagin's minimum principle. However, none of the current studies deal with multiobjective optimization of a diafiltration process in the presence of membrane fouling.…”
Section: Introductionmentioning
confidence: 99%